2015
DOI: 10.1007/s00421-015-3249-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-local muscle fatigue: effects and possible mechanisms

Abstract: While the NLMF literature is conflicting, certain variables appear to affect NLMF responses which can account for some of the discrepancies. Furthermore, the NLMF effects may be attributed to four different but interconnected pathways: neurological, biochemical, biomechanical and psychological.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 101 publications
6
99
1
Order By: Relevance
“…Although divergent findings exist (Halperin et al . ), this observation appears to agree with the idea that cross‐over fatigue (measured via reduced force during a single MVC or increased central fatigue) does not occur in the lower limb muscles (Regueme et al . ; Paillard et al .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although divergent findings exist (Halperin et al . ), this observation appears to agree with the idea that cross‐over fatigue (measured via reduced force during a single MVC or increased central fatigue) does not occur in the lower limb muscles (Regueme et al . ; Paillard et al .…”
Section: Discussionsupporting
confidence: 90%
“…2C and D). Although divergent findings exist (Halperin et al 2015), this observation appears to agree with the idea that cross-over fatigue (measured via reduced force during a single MVC or increased central fatigue) does not occur in the lower limb muscles (Regueme et al 2007;Paillard et al 2010;Amann et al 2013;Aboodarda et al 2015;Kennedy et al 2015;Prieske et al 2017). Given that no changes were observed for measures of central fatigue (VA PNS and VA TMS ) following LL condition ( Fig.…”
Section: Neuromuscular Performancesupporting
confidence: 82%
See 1 more Smart Citation
“…It is also feasible that training to MMF may impart greater adaptations in a contralateral limb due to potentially greater stimulus of centrally mediated neural factors through non local muscular fatigue (NLMF;Halperin et al, 2015). Whilst it is not within the scope of this article to provide extensive discussion, in brief; NLMF indicates a deficit in acute muscular performance in unexercised muscles as a result of exercising other (including contralateral) muscle groups (see Halperin et al, 2015 for a comprehensive review).…”
Section: R a F Tmentioning
confidence: 99%
“…Finally, the cognitive demand required for maximal contraction has been argued to differ from that required for submaximal contraction 30) . Additionally, Matsuura et al 31) have suggested that changes in cognitive process by heat exposure alter power profiles, but not peak and mean power output, during each cycling sprint in RCS.…”
Section: Perspective For Further Researchmentioning
confidence: 99%